'See and read this book': Reading the typography of English, 1509–1592 - Misson, J (2020)
This thesis gives a timeline of English typography between 1509 and 1592, and uses it to examine some ways sixteenth-century typography could and can be read. It is founded on a database of typographic descriptions of 10,645 books printed in England or English between 1509 and 1592, representing 82% of known editions for this period.